The Effect of Coconut Shell Liquid Smoke Concentration on the Sensory Characteristics and Total Bacterial Count of Catfish Meatballs Substituted with Oyster Mushrooms During Storage - Anindita Wahyu Noer Anggraini; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aimed to determine the effect of coconut shell liquid smoke concentration on the sensory characteristics at Day 0 and the total bacterial count during storage of catfish meatballs substituted with oyster mushrooms. A completely randomized design was used with treatments of 0.5%, 1%, 1.5%, and 2% (v/v) coconut shell liquid smoke. Sensory evaluation was conducted at Day 0 using a hedonic scale with 30 semi-trained panelists who evaluated color, aroma, taste, and texture. Sensory data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test (DMRT) at a 5% significance level. The treatment with the best sensory characteristics was selected using the De Garmo Effectiveness Index and subsequently evaluated for total bacterial count during 12 days of storage at 6°C and 30°C. The best treatment was 1.5% coconut shell liquid smoke, with sensory scores of 4.43 (somewhat like) for color, 4.90 (like) for aroma, 5.30 (like) for taste, and 4.83 (like) for texture. At 30°C, total bacterial count increased from a baseline of 3.70 log CFU/g to 7.30 log CFU/g on Day 4, remained at 7.30 log CFU/g on Day 8, and reached 8.10 log CFU/g on Day 12. At 6°C, total bacterial count increased from 3.70 log CFU/g to 4.42 log CFU/g, 4.67 log CFU/g, and 5.19 log CFU/g on Days 4, 8, and 12. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production